Non-binary modulation-coded scheme for the space two-way relay channels - Lei YANG; Song JIN; Bo-yang CAI; Jian-ping AN (Tongxin xuebao)
A non-binary irregular repeat-accumulate (IRA) modulation-coded physical-layer network coding (PNC) scheme was proposed for the space two-way relay channels (TWRC) to improve the information exchange rates of space information networks.In the scheme,a same non-binary IRA modulation code was employed at two users.This configuration enabled the recovery of the network coded information sequence from the superimposed signal directly by the relay.The optimized non-binary IRA modulation code was obtained by using extrinsic information transfer (EXIT) chart analysis.Numerical results demonstrate that the proposed scheme can reduce the duration of information exchange by about 48% compared to the conventional time divided multiple access scheme.